Research on Realistic Nod with Receptionist Robot SAYA That Has Human-like Appearance - TSUJI, Toshiaki; HIRAMATSU, Sachio; HASHIMOTO, Takuya; KOBAYASHI, Hiroshi (Transactions of the Japan Society of Mechanical Engineers Series C, 2007)
In face-to-face communication, the speaker as well as the listener nods during conversation. We refer to such behavior as “Speaker's nod”. In this paper, a “Speaker's nod” is realized as a natural interpersonal behavior in the receptionist robot SAYA, which has human-like appearance. First, we investigated the timing, angle and angular velocity of the human “Speaker's nod”. Based on the results, we developed a “Speaker's nod” function for SAYA. As a result, we found that “Speaker's nod” appears at the end of utterance frequently and appropriate nod-angle and angular velocity improve the humanness of SAYA. We then confirmed the effectiveness of “Speaker's nod” by a subjective experiment. The results indicate that appropriate nod timing, angle and angular velocity improve not only the humanness but also communicative effectiveness of SAYA in face-to-face communication with humans